Infiltration of the spinal cord and peripheral nerves in multiple myeloma - Su, Xiaoyun; Kong, Xiangquan; Kong, Xiangchuang; Lu, Zuneng; Zheng, Chuansheng (Frontiers in Oncology, 2022)
Background Multiple myeloma (MM) is a hematological malignancy, and intramedullary spinal cord metastasis is extremely rare. Methods Clinical and radiological data were collected from electronic medical records as well as a literature review of reported cases. Results We report a rare case of IgA-LAM stage IIB MM with involvement of the spinal cord and peripheral nervous system. Laboratory studies showed elevated levels of serum β2-macroglobulin and cerebrospinal fluid protein. Electromyography revealed a demyelinating process with motor conduction blocks. On MRI, the lesions of MM bone marrow are characterized as a type of diffuse infiltration. MR neurography demonstrated an enhanced nodule in the thoracic segment with swelling of the cervicothoracic segments of the spinal cord. Moreover, swelling and hypertrophy of the entire nerve branchial, lumbosacral plexus, and cauda equina were detected, accompanied by myofascitis and denervated muscles. Ultimately, the condition of the patient deteriorated quickly and she died with a diagnosis of refractory MM. Conclusion MRI not only has the advantage of displaying the primary involved site of the bone marrow but also facilitates detecting extramedullary hematopoietic MM, such as infiltrating sites of the central and/or peripheral nervous system.